A clinical case of repeat use of PARP inhibitors in a patient with mBRCA-associated ovarian cancer - A. B. Villert; I. A. Kolomiets; Y. A. Fesik; A. A. Ivanova; N. V. Yunusova; О. N. Churuksaeva (Сибирский онкологический журнал)
Backgraound. High-grade serous ovarian carcinoma (HGSOC) is the most common type of ovarian cancer. The prevalence of BRCA1/2 germline mutations is the highest in HGSOC. patients with germline BRCA gene mutations are more likely to respond to platinum-based chemotherapy. Clinical trials demonstrate the effectiveness of PARP inhibitors in the treatment of BRCA-associated ovarian cancer. Re-administration of PARP inhibitors after response to platinum-based chemotherapy demonstrates an increase in progression-free survival rates regardless of BRCA status. it is important for understanding the development of molecular mechanisms of resistance to platinum drugs and PARP inhibitors, as well as for developing new treatment strategies  and  tools  to  overcome  resistance. Case  description. This  clinical  case  of  BRCA-associated hereditary ovarian cancer demonstrates the efficacy and good tolerability of PARP inhibitor maintenance therapy following the treatment of the first relapse, as well as the efficacy of re-administration of PARP inhibitors following the treatment of the second relapse. The short-course of re-treatment with PARP inhibitors was accompanied by the development of multidrug resistance. the overall survival time was 112 months. Conclusion. The presence of mutations in BRCA1/2 genes is a promising justification for the administration of maintenance therapy with PARP inhibitors. Re-administration of PARP inhibitor maintenance therapy for relapsed ovarian cancer is currently being considered as a possible therapeutic option. deciphering the molecular mechanisms of resistance to PARP inhibitors is of paramount importance for the development of new treatment strategies and tools to overcome chemoresistance, re-sensitization of the tumor to platinum-based drugs or PARP inhibitors.